Television from the Trenches: An Archival Review of No Price Too High - Epp, Kathleen (Archivaria, 2000)
This review article examines the use of archival sources for the television documentary No Price Too High: Canadians and the Second World War, which first aired in 1996. The author is guided by the contextual approach to records, which is based on knowledge of the origin, original purposes, and characteristics of records.The article contends that some of the most effective stories in the documentary are those which respect the original nature and provenance of records and make explicit the connections between related records. RÉSUMÉ Ce commentaire critique examine l'utilisation des sources archivistiques dans le documentaire télévisuel Le Prix de la liberté: les Canadiens et la Deuxième guerre mondiale qui a été diffusé pour la première fois en 1996. L'auteure se guide sur une approche contextuelle des documents, laquelle est basée sur une connaissance de l'origine, les buts premiers et les caractéristiques des documents. L'article prétendque plusieurs des histoires les mieux rendus du documentaire sont celles qui respectentla nature originale et la provenance des documents et qui explicitent les connexionsentre eux.